Interface control and photovoltaic properties of n-type silicon/metal junction by organic dye - Yakuphanoğlu, Fahrettin; Ocak, Y. S.; Kilicoglu, T.; Farooq, W. A. (Elsevier, 2011)
The electronic parameters and photovoltaic properties of the Au/methylene blue/n-Si diodes were investigated by current-voltage and capacitance-conductance-frequency techniques. The diode exhibits a non-ideal behavior due the series resistance, organic layer and oxide layer. The barrier height (1.04 eV) of the Au/methylene blue/n-Si is higher than that of Au/n-Si Schottky diode (0.83 eV) due to an excess barrier formed by organic layer. The interface state density of the diode was determined using a conductance technique and was found to be 3.25 x 10(12) eV(-1) cm(-2). The diode shows a photovoltaic behavior with a maximum open circuit voltage V-oc of 0.23 V and short-circuit current I-sc of 20.8 mu A under 100 mW/cm(2). It is evaluated that Au/methylene blue/n-Si is an organic-on-inorganic photodiode with the obtained electronic parameters and methylene blue organic dye controls the interface and electrical properties of conventional metal/n-type silicon junction. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Inorganic-organic diode; Organic semiconductors; Interface state properties